Inhibitory effect of three strains of biocontrol microbes on pathogens causing rhizome rot of Polygonatum cyrtonema - Zheng, Meng-Qi; Jiang, Ren-Qiang; Fang, Wei; Chen, Jia-Yin; Zhao, Meng-Li; Si, Jin-Ping; Wu, Ling-Shang; Xu, Qiu-Fang (Zhongguo zhongyao zazhi, 2023)
Rhizome rot is one of the main disease in the cultivation of Polygonatum cyrtonema, and it is also a global disease which seriously occurs on the perennial medicinal plants such as Panax notoginseng and P. ginseng. There is no effective control method at present. To identify the effects of three biocontrol microbes(Penicillium oxalicum QZ8, Trichoderma asperellum QZ2, and Brevibacillus amyloliquefaciens WK1) on the pathogens causing rhizome rot of P. cyrtonema, this study verified six suspected pathogens for their pathogenicity on P. cyrtonema. The result showed that Fusarium sp. HJ4, Colletotrichum sp. HJ4-1, and Phomopsis sp. HJ15 were the pathogens of rhizome rot of P. cyrtonema, and it was found for the first time that Phomopsis sp. could cause rhizome rot P. cyrtonema. Furthermore, the inhibitory effects of biocontrol microbes and their secondary metabolites on three pathogens were determined by confrontation culture. The results showed that the three tested biocontrol microbes significantly inhibited th